Homelessness and identity construction among street children - Joshi, Sudarshan (Research Nepal Journal of Development Studies, 2021)
This paper aims to explore the process of identity construction and its form among homeless street children. In order to explore the process of identity construction and its forms this paper reviews key literatures on the issue. The study is comprehensively based on secondary information using the thematic analysis of five elements activity, food, looks, name and places. Based on the contents analyzed the identity of homeless street children constructed through the process; where they live, what they do, what they eat, what they wear, where they sleep, what name they call and what they look. Therefore, Homeless street children, Rag picker, Magne, Khate, Sadakchap, Bebarise, Tuhuro have the collective identities and the identity of any individual is multiple and fluid. The key forms of identities observed are five in number: - activity, food, looks, name and places. They live in street or public place. They do begging, collection of garbage, thieving and racking others. They eat junk and unhealthy food bay begging. They wear dirty cloth roughly.